PENGARUH PEMBERIAN KALSIUM KLORIDA DAN PENGHAMPAAN UDARA TERHADAP MUTU BUAH TOMAT - Rachel Breemer; Priscillia Picauly; Febby J. Polnaya (Universitas Pattimura, 2015)
This study aims to determine the level of concentration of calcium chloride and vacuum air on the quality of tomatoes. Post-harvest handling of tomatoes was done by giving treatment concentration of calcium chloride solution different (0, 6, 9, 12%) and determined the best treatment then treated with vacuum air (430, 540, 650, and 760 mm Hg). Observations were made of the color, hardness and weight loss. The results showed that the use of calcium chloride with vacuum air significant effect on the value of color, hardness and changes in fruit weight. The use of calcium chloride with a concentration of 12% is the best, because it can maintain the color values of 6.02%, 7.76% hardness, and can press the fruit weight loss of 1.04%. The level of vacuum air 430 mm Hg can maintain the color values of 6.79 and can reduce fruit weight loss of 2.95%.